An optimistic future of C4 crop broomcorn millet (Panicum miliaceum L.) for food security under increasing atmospheric CO2 concentrations - Shi,Xinrui; Shen,Jie; Niu,Bingjie; Lam,Shu Kee; Zong,Yuzheng; Zhang,Dongsheng; Hao,Xingyu; Li,Ping (PeerJ, 2022)
Broomcorn millet, a C4 cereal, has better tolerance to environmental stresses. Although elevated atmospheric CO2 concentration has led to grain nutrition reduction in most staple crops, studies evaluating its effects on broomcorn millet are still scarce. The yield, nutritional quality and metabolites of broomcorn millet were investigated under ambient CO2 (aCO2, 400 µmol mol–1) and elevated CO2 (eCO2, aCO2+ 200 µmol mol–1) for three years using open-top chambers (OTC). The results showed that the yield of broomcorn millet was markedly increased under eCO2 compared with aCO2. On average, eCO2 significantly increased the concentration of Mg (27.3%), Mn (14.6%), and B (21.2%) over three years, whereas it did not affect the concentration of P, K, Fe, Ca, Cu or Zn. Protein content was significantly decreased, whereas starch and oil concentrations were not changed by eCO2. With the greater increase in grain yield, eCO2 induced increase in the grain accumulations of P (23.87%), K (29.5%), Mn (40.08%), Ca (22.58%), Mg (51.31%), Zn (40.95%), B (48.54%), starch (16.96%) and oil (28.37%) on average for three years. Flavonoids such as kaempferol, apigenin, eriodictyol, luteolin, and chrysoeriol were accumulated under eCO2. The reduction in L-glutamine and L-lysine metabolites, which were the most representative amino acid in grain proteins, led to a reduction of protein concentration under eCO2. Broomcorn millet has more desirable nutritional traits for combating hidden hunger. This may potentially be useful for breeding more nutritious plants in the era of climate change.
Keywords: Elevated CO2 concentrations; Broomcorn millet; Quality; Nutrients; Metabolites